Implementing enterprise risk management from methods to applications - Lam, James (Wiley, 2017)
Enterprise risk management (ERM) is a complex yet critical issue that all companies must deal with in the twenty-first century. Failure to properly manage risk continues to plague corporations around the world. ERM empowers risk professionals to balance risks with rewards and balance people with processes.But to master the numerous aspects of enterprise risk management, you must integrate it into the culture and operations of the business. No one knows this better than risk management expert James Lam, and now, with Implementing Enterprise Risk Management: From Methods to Applications, he distills more than thirty years' worth of experience in the field to give risk professionals a clear understanding of how to implement an enterprise risk management program for every business. -- Provided by publisher.